A Reflection on Teacher Questioning Types - Roostini, Kasih Elisabeth (Universitas Pendidikan Indonesia, 2011)
Abstract This small-scale research is expected to serve as a reflective means for teachers so that they can explore their questioning types in their own classroom. It analyzed questioning types used by three teachers of general English classes. The questioning types were classified based on three dimensions—purpose, form, and function. The purpose-based questioning types, based on Long and Sato’s findings (1983), were classified into two: referential and display. The form-based questioning types, based on the classification of question types by Celce-Murcia and Larsen-Freeman (1999) and Biber et al. (1999), were classified into four major types: yes/no-questions, wh-questions, tag questions, and alternative questions. The function-based questioning types, based on Long and Sato’s findings (1983), were classified into three sub-types: comprehension checks, confirmation checks, and clarification requests. The data, obtained from three recorded class meetings, were transcribed and analyzed to see what questioning types each teacher employed and to obtain the number and percentage distribution of questioning types each teacher used. The results showed that referential questions were more frequently used than display questions at higher levels. There were a substantial number of incomplete questions, a form-based questioning type that did not belong to the classification of form-based questioning types employed in this study. The predominant use of incomplete questions in a communicative classroom should be reviewed as this questioning type required accuracy, rather than promoting language practice. The third type, the function-based questioning types, did not occur frequently at all the three stages. This study suggests that teachers use incomplete questions less frequently and try to use other form-based questioning types. It also encourages teachers to reflect on their own teaching and pursue their professional development. Keywords: teacher reflection, questioning types, teacher questions